Changes in dimensional stability of Pinus roxburghii sarg. and Mangifera indica L. woods after retification. (November 2014) - Tripathi, S.; Bhoru, Y. U.
Abstract : The present study was conducted to investigate the influence of heat treatment temperature and duration on the dimensional stability of chir pine ( Pinus roxburghii Sarg.) and mango ( Mangifera indica L.) wood. For this purpose, wood was heated at different temperatures for periods of 4, 8 and 12 h in an inert atmosphere. Differential responses of both wood species to different parameters, namely, volumetric swelling and shrinkage, water absorption and equilibrium moisture content (EMC) at different relative humidities, were observed. Results revealed that increase of heat treatment temperature in conjunction with time leads to a significant drop in the shrinkage of mango wood, whereas a reverse trend prevailed in chir pine until 210°C for 12 h treatment. Least values of EMC were recorded for chir pine and mango wood treated at 190 and 210°C for 4 h respectively. Further, increase in temperature and/or time of treatment significantly decreased the water absorption capacity of mango wood.